The Garden of the Mosques : Hafiz Hüseyin al-Ayvansarayî's Guide to the Muslim Monuments of Ottoman Istanbul - Crane, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This is an annotated translation of what is perhaps the most important Ottoman literary source for the Islamic monuments of the Ottoman capital, Istanbul: Hafız Hüseyin bin Ismail Ayvansarayî's Hadikat al-Cevami (The Garden of Mosques). Long recognized by Turkish scholars as a unique source for the city's architecture and urban form, the text, which was completed in 1195/1780 and revised and enlarged between 1248/1832-33 and 1253/1838 by Ali Sati, contains separate descriptions of each of Istanbul's more than 800 mosques, plus accounts of its medreses, tombs, tekkes and other monuments. The annotations place each of these buildings within the city's urban plan and provide biographical information about the patrons, architects and other personalities mentioned in the text. An introductory essay gives an account of Ayvansarayî's life and works, describes the various manuscript versions of the text and reviews the cartographic resources available for the study of Istanbul's urban form.